2007
DOI: 10.1021/bc700184b
|View full text |Cite
|
Sign up to set email alerts
|

A Macrophage−Nanozyme Delivery System for Parkinson's Disease

Abstract: Selective delivery of antioxidants to the substantia nigra pars compacta (SNpc) during Parkinson's disease (PD) can potentially attenuate oxidative stress and as such increase survival of dopaminergic neurons. To this end, we developed a bone-marrow-derived macrophage (BMM) system to deliver catalase to PD-affected brain regions in an animal model of human disease. To preclude BMMmediated enzyme degradation, catalase was packaged into a block ionomer complex with a cationic block copolymer, polyethyleneimine-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
173
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(179 citation statements)
references
References 89 publications
6
173
0
Order By: Relevance
“…Hence, it is possible to use macrophages as drug carriers for the delivery of various therapeutic payloads [96]. Batrakova et al delivered catalase using bone-marrow-derived macrophage (BMM) systems to PD-affected brain regions in an animal model [97]. The self-assembled catalase/polymer complexes referred to as nanozymes that were 60-100 nm in size were taken up by the BMMs and showed sustained release for about 24 hours as compared to immediate degradation of the free enzyme [97].…”
Section: Passive Targeting (Macrophage Loaded)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is possible to use macrophages as drug carriers for the delivery of various therapeutic payloads [96]. Batrakova et al delivered catalase using bone-marrow-derived macrophage (BMM) systems to PD-affected brain regions in an animal model [97]. The self-assembled catalase/polymer complexes referred to as nanozymes that were 60-100 nm in size were taken up by the BMMs and showed sustained release for about 24 hours as compared to immediate degradation of the free enzyme [97].…”
Section: Passive Targeting (Macrophage Loaded)mentioning
confidence: 99%
“…Batrakova et al delivered catalase using bone-marrow-derived macrophage (BMM) systems to PD-affected brain regions in an animal model [97]. The self-assembled catalase/polymer complexes referred to as nanozymes that were 60-100 nm in size were taken up by the BMMs and showed sustained release for about 24 hours as compared to immediate degradation of the free enzyme [97]. This had implications in decomposition of microglial hydrogen peroxide that could reduce oxidative stress in PD.…”
Section: Passive Targeting (Macrophage Loaded)mentioning
confidence: 99%
“…[89] Peritoneal macrophages have also been used to deliver liposomal doxorubicin to both subcutaneous and metastatic models of lung carcinoma [90]. Batrakova and colleagues have reported that macrophages can be loaded ex vivo with a self-assembled catalase/PEI-PEG complex, penetrate the blood brain barrier, and deliver the catalase to diseased neurons in an Parkinson's disease model [91]. A similar approach could be potentially used to deliver a prodrug activating enzyme or other protein therapy to tumors without introducing a foreign gene into the homing cells.…”
Section: Monocytesmentioning
confidence: 99%
“…Based on this, our laboratories developed cell mediated delivery of catalase nanozyme to the brain to mitigate production of ROS and induce neuroprotection (Batrakova et al 2007). To preclude BMM-mediated enzyme degradation, catalase was packaged into a block ionomer complex with a cationic block copolymer, PEI-PEG.…”
Section: Cells and Nanomaterials Hybrids For Clinical Neurosciencementioning
confidence: 99%